Dyslipidemia and Other Parameters in Women With Pregnancy Induced Hypertension - Alaa Saber Shihab; Maha Arshad Hamdi; Abdulhadi Mohamed Jumaa; Mousa Mahmoud Marbut; Sahar Kamel Jwad (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Several investigations have confirmed changes in lipid profiles and other markers (IL-6,CRP ) in women with pregnancy-induced hypertension (PIH). Although, the cause-and-effect correlations between these lipid profiles and other markers with the PIH are yet unknown.Aim: To study the relationship of  serum lipid profile ,C- reactive protein (CRP )and interleukin-6 (IL-6 ) with pregnancy-induced hypertension.Patients and Methods: A cross- sectional study, was done on 60 pregnant women  attending with pregnant induce hypertension (PIH) treated in General Salah Alden  Hospital in Tikrit city-Iraq, from January 2021 to April 2021. Other 60 normal pregnant women, at the same period, were selected as a control group. The average age of the participants was (27.1±5.0) years, all the taken blood samples , were examined for lipid profile, CRP and IL-6.Results: Statistically show significant differences in IL-6 level and CRP. Whereas Lipid profile(TG ,LDL-C  HDL-C ,TC and VLDL) were found, also, significant differences  in PIH patients as compared to normal  controls.